2016
DOI: 10.3895/rbfta.v3n1.3768
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of Nafion® membrane as a function of water content by Phase-Resolved Photoacoustic Method

Abstract: Nafion® membranes were developed by DuPont, a perfluorosulfonic acid/polytetrafluoroethylene copolymer. These membranes are hydrophilic and the water is preferentially sorbed into the clusters due to the hydrophobic character of fluorocarbon matrix. The sulfonic acid groups are chemically active and fixed within the Teflon polymer matrix. Thus, this first synthetic ionic polymer is chemically resistant and durable, making it useful for Proton Exchange Membrane fuel cells. In order to monitoring the groups -OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…1 for pristine membrane and hydrous 1 in 1 h up to 11 h and 24–25 h as reported elsewhere. 15 We found that the stretching modes and combinations O–H dominate the region of 800–2600 nm and we cataloged and categorized 13 peaks in these regions. Overall, to avoid heating and allow the cooling of the membrane, the results revealed an optimum point of the OH absorption band alongside with a higher thermal diffusivity and before saturation of the membrane, i.e., approximately 1 h of hydration.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 for pristine membrane and hydrous 1 in 1 h up to 11 h and 24–25 h as reported elsewhere. 15 We found that the stretching modes and combinations O–H dominate the region of 800–2600 nm and we cataloged and categorized 13 peaks in these regions. Overall, to avoid heating and allow the cooling of the membrane, the results revealed an optimum point of the OH absorption band alongside with a higher thermal diffusivity and before saturation of the membrane, i.e., approximately 1 h of hydration.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal analysis experiments were performed using the assays described in Table I after PA results were obtained elsewhere. 15 The samples were discs measuring 3 mm diameter. The TG-DSC experiments were carried out in the following conditions: heating rate of 20 C min À1 , alumina (Al 2 O 3 ) crucibles of open capsule type, under argon atmosphere at 30 cm 3 min À1 , temperature range from 30 C (the membranes were maintained at 30 C for 300 s) to 700 C. The thermal analyzer was calibrated using nickel as standard (Curie temperature 354 C).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations